Vasohibin 2 promotes human luminal breast cancer angiogenesis in a non-paracrine manner via transcriptional activation of fibroblast growth factor 2. Issue 2 (28th December 2016) - Tu, Min; Lu, Cheng; Lv, Nan; Wei, Jishu; Lu, Zipeng; Xi, Chunhua; Chen, Jianmin; Guo, Feng; Jiang, Kuirong; Li, Qiang; Wu, Junli; Song, Guoxin; et al.
Abstract: Vasohibin 2 (VASH2) is an angiogenic factor and cancer-related protein that acts via paracrine mechanisms. Here, we investigated the angiogenic function and mechanism of action of VASH2 in 200 human breast cancer tissues by performing immunohistochemical staining, western blot, indirect sandwich enzyme-linked immunosorbent assay (ELISA), and a semi-quantitative sandwich-based antibody array. Breast cancer cells stably overexpressing VASH2 or with knocked-down VASH2 were established and used for in vivo and in vitro models. In human luminal tissue, but not in HER2-positive or basal-like breast cancer tissues, VASH2 was positively correlated with CD31-positive microvascular density, induced angiogenesis in xenograft tumors, and promoted human umbilical vein endothelial cell tube formation in vitro . VASH2 expression was absent in the concentrated conditioned medium collected from knocked-down VASH2 and VASH2-overexpressing luminal breast cancer cells. Further, VASH2 regulated the expression of fibroblast growth factor 2 (FGF2) in human luminal breast cancer cells, and the pro-angiogenic effect induced by VASH2 overexpression was blocked by FGF2 neutralization in vitro . Additionally, dual luciferase reporter assay and Chromatin immunoprecipitation analysis results showed that FGF2 promoter was transcriptionally activated by VASH2 via histone modifications. In conclusion, VASH2 expression is positively correlated with FGF2 expression and promotes angiogenesis in human luminal breast cancer by transcriptional activation of fibroblast growth factor 2 through non-paracrine mechanisms. Highlights: VASH2 correlated positively with CD31 expression in human luminal breast cancer tissues. VASH2 promoted angiogenesis via activation of FGF2 in human luminal breast cancer cells through a non-paracrine manner. VASH2 correlated positively with FGF2 expression in human luminal breast cancer tissues.